2022
DOI: 10.1093/procel/pwac020
|View full text |Cite
|
Sign up to set email alerts
|

Single-dose AAV-based vaccine induces a high level of neutralizing antibodies against SARS-CoV-2 in rhesus macaques

Abstract: Coronavirus disease 2019 (COVID-19), which is triggered by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, continues to threaten global public health. Developing a vaccine that only requires single immunization but provides longterm protection for the prevention and control of COVID-19 is important. Here, we developed an adeno-associated virus (AAV)-based vaccine expressing a stable receptorbinding domain (SRBD) protein. The vaccine requires only a single shot but provides effective neu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Many types of vaccines have been developed to control the infection and spread of SARS-CoV-2, including vaccines based on messenger RNA (mRNA) 3 , viral vectors 4,5 , recombinant proteins 6 , and inactivated SARS-CoV-2 7 . Immunization with these vaccines showed a reduction in infection rates and post-infection mortality.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many types of vaccines have been developed to control the infection and spread of SARS-CoV-2, including vaccines based on messenger RNA (mRNA) 3 , viral vectors 4,5 , recombinant proteins 6 , and inactivated SARS-CoV-2 7 . Immunization with these vaccines showed a reduction in infection rates and post-infection mortality.…”
mentioning
confidence: 99%
“…To test the antibody level against different variants of SARS-CoV2, we collected the plasma of 41 infected patients (11 unvaccinated patients, 7 with 2-dose inactivated SARS-CoV2 vaccine, 13 with 3-dose inactivated SARS-CoV2 or recombinant protein vaccine and 10 with 4-dose inactivated SARS-CoV2 or recombinant protein vaccine) and 15 uninfected people, including 10 people received the latest boost (4 th dose) less than 3 months and 5 people received the latest boost more than 6 months. We then tested the antibody titer (IgG) in the plasma against the prototype, Omicron BA.5, BF.7, and XBB 1.5 variants using ELISA test 4 . Surprisingly, we found that the antibody level against Omicron BA.5, BF.7, and XBB 1.5 of the individuals has a high positive correlation with the antibody level against prototype SARS-CoV2 (Figure 1 F).…”
mentioning
confidence: 99%